MOBILE MARRIAGE ITSBAT SESSION: ITS IMPORTANCE FOR THE UNREGISTERED MARRIAGES - Jamaluddin T (Al-Bayyinah, 2020)
AbstractMarriage itsbat is a solution to unregistered marriages. Mandate of Law No. 1 of 1974 concerning marriages has required marriages to be recorded, as a form of marriage validity that is recognized by the State. The government's program through the judiciary to conduct marital itsbat for the unregistered marriage. This was facilitated by the implementation of mobile marriage itsbat session for unregistered marriages. An unregistered marriage is ratified through a mobile court integrated service conducted by the Religious Court in the case of marriage law. This study more specifically examines the phenomenon of marriage itsbat through a mobile court session of unregistered marriages in Bone Regency and the application of PERMA No. 1 of 2015 concerning Integrated Service of the Mobile Session, which is focused in the Religious Court Class 1A of Watampone in realizing marriage ratification. This research is a qualitative research in the field of law. Research data were collected through in-depth interviews with Watampone religious court judges, religious counselors and the community. The findings of this study indicate that the urgency of marriage itsbat in the Watampone Religious Court has succeeded in ratifying the marriage of 677 cases that are relevant to PERMA regarding Integrated Service of the Mobile Session. This finding has implications for minimizing the number of unregistered marriages and giving birth to public awareness of the importance of the legal legality of a marriage.Keywords: Marriage itsbat; Mobile Court Session; Watampone Religious Court.